Pengaruh Kualitas Produk, Keterjangkauan Harga, Online Customer Rating Dan Digital Marketing Terhadap Minat Beli Produk Di Online Shop Shopee (Studi Kasus pada Masyarakat di Desa Bolo) - Eva Prihatiningsih; Harries Arizonia Ismail (Yayasan Sagita Akademia Maju, 2024)
This study aims to examine the influence of product quality, price affordability, online customer ratings, and digital marketing on purchase intention for products on the Shopee online shopping platform. The research sample consisted of 100 Shopee users in Desa Bolo, Demak Regency, selected using the Slovin formula. Data were collected through questionnaires with a Likert scale. The findings revealed that product quality, price affordability, online customer ratings, and digital marketing positively and significantly influence purchase intention. Based on regression analysis, product quality (β = 0.504), price (β = 0.118), online customer ratings (β = 0.206), and digital marketing (β = 0.281) each significantly impact purchase intention. These findings provide insights for e-commerce companies to enhance these factors in their marketing strategies to attract consumer purchase intentions.